2019
DOI: 10.1093/femsle/fnz059
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas, a highly effective tool for genome editing in Clostridium saccharoperbutylacetonicum N1-4(HMT)

Abstract: The solventogenic clostridia have long been known for their ability to convert sugars from complex feedstocks into commercially important solvents. Although the acetone-butanol-ethanol process fell out of favour decades ago, renewed interest in sustainability and ‘green’ chemistry has re-established our appetite for reviving technologies such as these, albeit with 21st century improvements. As CRISPR-Cas genome editing tools are being developed and applied to the solventogenic clostridia, their industrial pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…As a priority choice, a point mutation design could be achieved by introducing changes at the first or second position of PAMs. Combining the changes within PAMs and the seed region could even increase the efficiency of editing, as reported for other endogenous CRISPR editing tools (21,25). We have previously shown that a nonfunctional PAM and mutation in the first position of protospacer within the seed region abolished or considerably impaired CRISPR interference (15).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As a priority choice, a point mutation design could be achieved by introducing changes at the first or second position of PAMs. Combining the changes within PAMs and the seed region could even increase the efficiency of editing, as reported for other endogenous CRISPR editing tools (21,25). We have previously shown that a nonfunctional PAM and mutation in the first position of protospacer within the seed region abolished or considerably impaired CRISPR interference (15).…”
Section: Discussionmentioning
confidence: 66%
“…Another advantage of this approach is that there is no need to heterologously express potentially toxic Cas proteins inside bacterial or archaeal cells. The genome editing approach based on an endogenous CRISPR-Cas system was successfully applied in several prokaryotic organisms using CRISPR-Cas subtype I-A and III-B or subtype I-B in archaea, Sulfolobus islandicus (21) and Haloarcula hispanica (22), respectively, and subtype I-B in several clostridial species, C. pasteurianum (23), C. tyrobutyricum (24), and C. saccharoperbutylacetonicum (25).…”
mentioning
confidence: 99%
“…In this experiment, the butanol concentration in the media was gradually increased over a period of several weeks and glycerol stocks were taken at different time points throughout the experiment. These cultures were then tested in bottle screens (method in [10]), to assay for improved sugar uptake rates (Fig. 1).…”
Section: Solventogenic Clostridiamentioning
confidence: 99%
“…This is a significant research area in the clostridial community with a number of examples being published, e.g. C. acetobutylicum [25], C. beijerinckii [25, 26], C. saccharoperbutylacetonicum [10, 27, 28], C. tyrobutyricum [29], C. pasteurianum [30], and C. ljungdahlii [31].…”
Section: Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation